Science and Psychic Phenomena: The Fall of the House of Skeptics by Chris Carter - Cardeña, Etzel (Journal of Scientific Exploration, 2013)
During a recent stroll through the Campo de' Fiori in Rome, few things could have been farther from my thoughts than writing this review. In the middle of the square, somewhere hidden between rows of fruit stands and tourists, however, stood Ferrari's monument to Giordano Bruno, the Dominican philosopher, mathematician, astronomer, astrologer, hermeticist, and mnemonist. Bruno was burned alive after the inquisitors inserted in his mouth an iron gag that pierced his tongue and palate. It goes beyond irony to read that in the year 2000 the second ranking Catholic, Cardinal Sodano, remarked that the inquisitors who tried Bruno "had the desire to serve freedom and promote the common good and did everything possible to save his life" (Seife, 2000).